In [6]:
using Plots, ApproxFun, SingularIntegralEquations, DifferentialEquations, ComplexPhasePortrait
gr();
Dr Sheehan Olver
s.olver@imperial.ac.uk
Website: https://github.com/dlfivefifty/M3M6LectureNotes
Take as an initial guess $$ \phi_1(z) = {\sqrt{z-1} \sqrt{z+1} \over 2\I(1 + z^2)} $$ This satisfies for $-1 < x < 1$ $$ \phi_1^+(x) -\phi_1^-(x) = { \sqrt{1-x^2} \over 2(1 + x^2)} - {- \sqrt{1-x^2} \over 2(1 + x^2)} = {\sqrt{1 - x^2} \over 1+x^2} $$
Further, as $z \rightarrow \infty$, $$ \phi_1(z) \sim {z \over \I(1+ z^2)} \rightarrow 0 $$
The catch is that it has poles at $\pm \I$: \begin{align*} \phi_1(z) = -{\sqrt{\I -1} \sqrt{\I+1} \over 4} { 1 \over z - \I} + O(1) \\ \phi_1(z) = {\sqrt{-\I -1} \sqrt{-\I+1} \over 4} { 1 \over z + \I} + O(1) \end{align*} Thus it follows that $$ \phi(z) = \phi_1(z) + {\sqrt{\I -1} \sqrt{\I+1} \over 4} { 1 \over z - \I} - {\sqrt{-\I -1} \sqrt{-\I+1} \over 4} { 1 \over z + \I} $$ is
By Plemelj II, this must be the Cauchy transform.
Demonstration We will see experimentally that it correct. First we do a phase plot to make sure we satisfy (Analyticity):
In [7]:
φ = z -> sqrt(z-1)sqrt(z+1)/(2im*(1+z^2)) +
sqrt(im-1)sqrt(im+1)/4*1/(z-im) -
sqrt(-im-1)sqrt(-im+1)/4*1/(z+im)
phaseplot(-3..3, -3..3, φ)
Out[7]:
We can also see from the phase plot (Regularity): we have weaker than pole singularities, otherwise we would have at least a full,counter clockwise colour wheel. We can check decay as well:
In [8]:
φ(200.0+200.0im)
Out[8]:
Finally, we compare it numerically it to cauchy(f, z)
which is implemented in SingularIntegralEquations.jl:
In [9]:
φ(2.0+2.0im)
Out[9]:
In [10]:
x = Fun()
cauchy(sqrt(1-x^2)/(1+x^2), 2.0+2.0im)
Out[10]:
Recall that $$ \psi(z) = {\log(z-1) - \log(z+1) \over 2 \pi \I} $$ satisfies $$ \psi_+(x) - \psi_-(x) = 1 $$ Therefore, consider $$ \phi_1(z) = {\psi(z) \over 2 + z} $$ This has the right jump, but has an extra pole at $z = -2$: for $x < -1$ we have $$ \phi_1(x) = {\log_+(x-1) - \log_+(x+1) \over 2 \pi \I} {1 \over 2 + x} = {\log(1-x) - \log(-1-x) \over 2 \pi \I} {1 \over 2 + x} $$ hence we arrive at the solution $$ \phi_1(z) - {\log 3 \over 2 \pi \I (2+z)} $$ We can verify that $\phi_1(\infty) = 0$.
In [11]:
φ = z -> (log(z-1)-log(z+1)) / ((2π*im)*(2+z)) - log(3)/(2π*im*(2+z))
phaseplot(-3..3, -3..3, φ)
Out[11]:
In [12]:
φ(2.0+2.0im)
Out[12]:
In [13]:
cauchy(1/(2+x), 2.0+2.0im)
Out[13]:
We first calculate the Cauchy transform of $f(x) = x/\sqrt{1-x^2}$: $$ \phi(z) = {\I z \over 2 \sqrt{z -1} \sqrt{z+1}} - {\I \over 2} $$ This vanishes at $\infty$ and has the correct jump. We then have $$ -\I{\cal H}f(x) = \phi^+(x) + \phi^-(x) = -\I $$ This implies that $$ \dashint_{-1}^1 {t \over (t-x) \sqrt{1-t^2}} \dt = \pi \HH f(x) = \pi $$
In [14]:
f = x/sqrt(1-x^2)
π*hilbert(f, 0.1)
Out[14]:
In [15]:
C = randn()
φ = z -> -z/(2*sqrt(z-1)*sqrt(z+1))+1/2 + C/(sqrt(z-1)*sqrt(z+1))
Out[15]:
In [16]:
φ(0.1+0.0im)+φ(0.1-0.0im)
Out[16]:
In [17]:
φ(1E8)
Out[17]:
In [18]:
C = randn()
φ = z -> z/(sqrt(z-1)*sqrt(z+1)) + C/(sqrt(z-1)*sqrt(z+1))
Out[18]:
In [19]:
φ(0.1+0.0im)+φ(0.1-0.0im)
Out[19]:
In [20]:
φ(1E9)
Out[20]:
For $f(x) = \sqrt{1-\diamond^2}$, we use the formula $$ \phi(z) = {\I \over \sqrt{z - 1} \sqrt{z+1}} \CC[\sqrt{1-\diamond^2} f](z) + {C \over \sqrt{z-1}\sqrt{z+1}} = {\I \over \sqrt{z - 1} \sqrt{z+1}} \CC[1-\diamond^2](z) + {C \over \sqrt{z-1}\sqrt{z+1}} $$ We already know $\CC1(z)$, and we can deduce $\CC[\diamond^2]$ as follows: try $$ \phi_1(z) = z^2 \CC1(z) = z^2 {\log(z-1) - \log(z+1) \over 2 \pi \I} $$ this has the right jump, but blows up at $\infty$ like: $$ x^2 (\log(x-1) - \log(x+1)) = x^2 (\log(1-1/x) - \log(1+1/x) ) = -2 x + O(x^{-1}) $$ using $$ \log z = (z-1) - {1\over 2}(z-1)^2 + O(z-1)^3 $$ Thus we have $$ \CC[\diamond^2](z) = {z^2 (\log(z-1) - \log(z+1)) + 2 z \over 2 \pi \I} $$ and $$ \phi(z) = {\I \over \sqrt{z - 1} \sqrt{z+1}} {(1-z^2)(\log(z-1) - \log(z+1)) - 2 z \over 2 \pi \I} + {C \over \sqrt{z-1}\sqrt{z+1}} $$
Demonstration Here we see that the Cauchy transform of $x^2$ has the correct formula:
In [21]:
z = 2.0+2.0im
cauchy(x^2, z)
Out[21]:
In [22]:
(z^2*(log(z-1)-log(z+1))+2z)/(2π*im)
Out[22]:
We now see that $\phi$ has the right jumps:
In [23]:
C = randn()
φ = z -> im/(sqrt(z-1)*sqrt(z+1)) * ((1-z^2)*(log(z-1)-log(z+1))-2z)/(2π*im) + C/(sqrt(z-1)sqrt(z+1))
Out[23]:
In [24]:
φ(0.1+0.0im) + φ(0.1-0.0im) - sqrt(1-0.1^2)
Out[24]:
Finally, it vanishes at infinity:
In [25]:
φ(1E5)
Out[25]:
Let $f(x) = {1 \over 1+x^2}$. From Problem 1.1 part 1 we know $$ \CC[\sqrt{1-\diamond^2}] f(z) = {\sqrt{z-1} \sqrt{z+1} \over 2\I(1 + z^2)} + {\sqrt{\I -1} \sqrt{\I+1} \over 4} { 1 \over z - \I} - {\sqrt{-\I -1} \sqrt{-\I+1} \over 4} { 1 \over z + \I} $$ hence from the solution formula we have $$ \phi(z) = {1 \over 2(1 + z^2)} + {\sqrt{\I -1} \sqrt{\I+1} \I \over 4\sqrt{z-1} \sqrt{z+1}} { 1 \over z - \I} - {\sqrt{-\I -1} \sqrt{-\I+1} \I \over 4\sqrt{z-1} \sqrt{z+1}} { 1 \over z + \I} + {C \over \sqrt{z-1} \sqrt{z+1}} $$
But we want something stronger: that $\phi(z) = O(z^{-2})$. To accomplish this, we need to choose $C$. Fortunately, I made the problem easy as every term apart from the last one is already $O(z^{-2})$, so choose $C = 0$:
In [26]:
φ = z -> 1/(2*(1+z^2)) +
sqrt(im-1)sqrt(im+1)*im/(4sqrt(z-1)sqrt(z+1))*1/(z-im) -
sqrt(-im-1)sqrt(-im+1)*im/(4sqrt(z-1)sqrt(z+1))*1/(z+im)
φ(1E5)*1E5^2
Out[26]:
We see also that it has the right jump:
In [27]:
φ(0.1+0.0im) + φ(0.1-0.0im)
Out[27]:
In [28]:
1/(1+0.1^2)
Out[28]:
In [29]:
t = Fun()
z = 2.0+2.0im
cauchy(t, z), z*(log(z-1)-log(z+1))/(2π*im) + 1/(im*π)
Out[29]:
Therefore, we have $$ \HH[\diamond](x) = \I (\CC^+ + \CC^-) \diamond(x) = x {\log(1-x) - \log(1+x) \over \pi} +{2 \over \pi} $$
In [30]:
x = 0.1
hilbert(t,x), x*(log(1-x)-log(1+x))/(π) + 2/π
Out[30]:
Therefore, we get $$ u(x) = - {x(\log(1-x) - \log(1+x))+2 \over \pi\sqrt{1-x^2}} - {C \over \sqrt{1-x^2}} $$ This can be verified in Mathematica via
NIntegrate[-((
x (Log[1 - x] - Log[1 + x]) +
2)/(π Sqrt[1 - x^2] (x - 0.1))), {x, -1, 0.1, 1},
PrincipalValue -> True]/π
In [31]:
t = Fun()
z = 2.0+2.0im
cauchy(sqrt(1-t^2)/(2+t), z), (sqrt(z-1)sqrt(z+1)-z)/(2im*(2+z)) + (sqrt(3)-2)/(2im*(z+2))
Out[31]:
Therefore, calculating $\I(\CC^+ + \CC^-)$ we find that $$ \HH\left[{\sqrt{1-\diamond^2} \over 2+\diamond}\right](z) = -{x\over 2+x} +{ \sqrt{3} -2 \over 2+x} $$
In [32]:
x = 0.1
hilbert(sqrt(1-t^2)/(2+t), x), -x/(2+x)+(sqrt(3)-2)/(2+x)
Out[32]:
Thus the general solution is $$ u(x) = {1 \over \sqrt{1-x^2}} \left( {x\over 2+x} -{ \sqrt{3} -2 \over 2+x} + C \right) $$ We need to choose $C$ so this is bounded at the right-endpoint: In other words, $$ u(x) = {1 \over \sqrt{1-x^2}} \left( {x\over 2+x} -{ \sqrt{3} -2 \over 2+x} +{ \sqrt{3} -3 \over 3} \right) $$
In [33]:
u = (t/(2+t)-(sqrt(3)-2)/(2+t)+(sqrt(3)-3)/3)/sqrt(1-t^2)
plot(u; ylims=(-5,5))
Out[33]:
In [34]:
x = 0.1
hilbert(u,x) , 1/(2+x)
Out[34]:
Doing the change of variables $\zeta = b s$ we have $$ \log(ab) = \int_1^{ab} {\D \zeta \over \zeta} = \int_{1/b}^a {\D s \over s} $$ if $\gamma$ does not surround the origin, we have $$ 0 = \oint_\gamma {\D s \over s} = \left[\int_1^{1/b} + \int_{1/b}^a + \int_a^1\right] {\D s \over s} $$ which implies $$ \log(ab) = \left[-\int_a^1 -\int_1^{1/b} \right] {\D s \over s} = \log a - \log {1 \over b} = \log a + \log b $$ Here's a picture:
In [35]:
a = 1.0+2.0im
b = -1.0-2.0im
@show log(a*b)
@show log(a) + log(b)
scatter([real(1/b)], [imag(1/b)]; label="1/b")
scatter!([real(a)], [imag(a)]; label="a")
scatter!([0.0], [0.0]; label="0")
plot!(Segment(1, 1/b) ∪ Segment(1/b, a) ∪ Segment(a, 1); label="contour")
Out[35]:
If it surrounds the origin counbter-clockwise, that is, it has positive orientation, we have $2\pi \I = \oint_\gamma {\D s \over s}$, which shoes that $$ \log(ab) = 2 \pi \I - \left[\int_a^1 +\int_1^{1/b} \right] {\D s \over s} = \log a + \log b + 2\pi \I $$ and a similar result when counter clockwise.
In [36]:
a = 1.0+2.0im
b = -2.0+2.0im
@show log(a*b)
@show log(a) + log(b) - 2π*im
scatter([real(1/b)], [imag(1/b)]; label="1/b")
scatter!([real(a)], [imag(a)]; label="a")
scatter!([0.0], [0.0]; label="0")
plot!(Segment(1, 1/b) ∪ Segment(1/b, a) ∪ Segment(a, 1); label="contour")
Out[36]:
If the contour passes through the origin, there are three possibility:
1. In the case where $a < 0$ and $b < 0$ (and hence $a b > 0$), perturbing $a$ above and $b$ below or vice versa avoids $\gamma$ winding around zero, so we have $$ \log(a b) = \log_+ a + \log_- b = \log_- a + \log_+ b = \log_+ a + \log_+ b - 2 \pi \I = \log_- a + \log_- b + 2 \pi \I $$
In [37]:
a = -2.0
b = -3.0
@show log(a*b)
@show log(a+0.0im) + log(b-0.0im)
@show log(a-0.0im) + log(b+0.0im)
@show log(a-0.0im) + log(b-0.0im) + 2π*im
@show log(a+0.0im) + log(b+0.0im) - 2π*im;
In the case where $a < 0$ and $b > 0$, then $ a b < 0$, but we can perturb $a$ above/below to get $$ \log_\pm(a b) = \log_\pm a + \log b $$ (and by symmetry, the equivalent holds for $b < 0$ and $a > 0$.)
In [38]:
a = -2.0
b = 3.0
@show log(a*b +0.0im)
@show log(a+0.0im) + log(b);
@show log(a*b -0.0im)
@show log(a-0.0im) + log(b);
In the case where $a < 0$, if $\Im b > 0$ we can perturb $a$ below so that $\gamma$ does not contain zero, giving us $$ \log(ab) = \log_- a + \log b $$ similarly, if $\Im b < 0$ we can perturb $a$ above.
In [39]:
a = -2.0
b = 3.0 + im
@show log(a*b)
@show log(a-0.0im) + log(b);
b = 3.0 + im;
@show log(a*b)
@show log(a+0.0im) + log(b);
2. In this case, swap the role of $a$ and $b$ and use the answers for $a < 0$.
3. Finally, we have the case $a b < 0$ and neither $a$ nor $b$ is real. Note that $$ ab = (a_x + \I a_y) (b_x + \I b_y) = a_x b_x - a_y b_y + \I(a_x b_y + a_yb_x) $$ It follows if $b_x > 0$ we have $$ (ab)_+ = a_+ b $$ and if $b_x < 0$ we have $$ (ab)_+ = a_- b $$
In [40]:
a = 1.0 + 1.0im
b = 1.0 + 1.0im
@show log(a*b + eps()im)
@show log((a+eps()im)*b)
Out[40]:
In [41]:
a = 1.0 + 1.0im
b = -1.0 + 1.0im
@show log(a*b + eps()im)
@show log((a-eps()im)*b)
Out[41]:
We can use this perturbation to reduce to the previous cases. For example, if $a = 1 + \I$ and $b = -1 + \I$, pertubing $ab$ above causes $a$ to be perturbed above, which causes the contour to surround the origin clockwise, hence we have $$ \log_+(ab) = \log(a)_+b = \log a b - 2 \pi \I $$
In [42]:
a = 1.0 + 1.0im
b = -1.0 + 1.0im
@show log(a*b - eps()im)
@show log(a)+log(b)-2π*im;
Use the contour $\gamma(t) = 1 + t(1-z)$ to reduce it to a normal integral: $$\overline{\log z } = \overline{\int_1^z {1 \over \zeta} \D \zeta} = \overline{\int_0^1 {(z-1) \over 1+(z-1) t} \dt} = \int_0^1 {(\bar z-1) \over 1+(\bar z-1) t} \dt = \int_1^{\bar z} {\D \zeta \over \zeta} = \log \bar z.$$ We then have, since the contour from $1$ to $1/(\bar z)$ to $z$ never surrounds the origin since both $\Im z$ and $\Im 1/(\bar z)$ have the same sign, we have $$ 2 \Re \log z = \log z + \overline{\log z} = \log z + \log \bar z = \log z \bar z = \log |z|^2 = 2 \log |z| $$ On the other hand, we have, where the contour of integration is chosen to be to the right of zero and then we do the change of variables $\zeta = |z| \E^{\I \theta}$ $$ 2 \Im \log z = \log z - \log \bar z = \int_{\bar z}^z {\D \zeta \over \zeta} = \I \int_{-\arg z}^{\arg z} \D \theta = 2 \I \arg z $$
We first show that it is analytic on $(-\infty,0)$. To do this, we need to show that the limit from above equals the limit from below: for $x < 0$ we have $$\log_1^+ x -\log_1^- x = \log_+x - \log_- x +2 \pi \I = 0$$ Then for $x > 0$ and using $\log_1^\pm(x) = \lim_{\epsilon\rightarrow 0} \log(x\pm \I \epsilon)$ we find $$ \log_1^+(x) - \log_1^-x = \log x- \log x- 2\pi \I = -2 \pi \I $$
Demonstration Here we see that the following is the analytic continuation:
In [43]:
log1 = z -> begin
if imag(z) > 0
log(z)
elseif imag(z) == 0 && real(z) < 0
log(z + 0.0im)
elseif imag(z) < 0
log(z) + 2π*im
else
error("log1 not defined on real axis")
end
end
Out[43]:
In [48]:
phaseplot(-3..3, -3..3, log1)
Out[48]:
In [49]:
log1(-2.0+0.0im)
Out[49]:
In [50]:
log1(-2.0-0.0im)
Out[50]:
In [51]:
log1(-2.0)
Out[51]:
In [52]:
log1(2.0+eps()im)
Out[52]:
In [53]:
log1(2.0-eps()im)
Out[53]:
0 & |z| > 0
\end{cases}
$$
hence $(\CC^+-\CC^-)1(\zeta) = 1$Suppose we have another solution $\phi$ and consider $\psi(z) = \phi(z) - \CC f(z)$. Then on the circle we have $$ \psi_+(\zeta) - \psi_-(\zeta) = \phi_+(\zeta) - \CC_+f(\zeta) - \phi_-(\zeta) + \CC_+f(\zeta) = f(\zeta)-f(\zeta) = 0 $$ Thus $\psi$ is entire, and since it decays at infinity, it must be zero by Liouville's theorem.
When $k \geq 0$, we have from 3.1 and 3.2 $$ \CC[\diamond^k](z) =\begin{cases} z^k & |z| < 0 \\ 0 & |z| > 0 \end{cases} $$ when $k < 0$ since $$\CC[\diamond^k]^+(\zeta) - \CC[\diamond^k]^-(\zeta) = \zeta^k - 0 = \zeta^k$$. we similarly have $$ \CC[\diamond^k](z) =\begin{cases} 0 & |z| < 0 \\ -z^k & |z| > 0 \end{cases} $$
Therefore, $$ \Im \CC^-[\diamond^k](\zeta) =\begin{cases} 0 & k \geq 0 \\ -{\zeta^k - \zeta^{-k} \over 2 \I} & k < 0 \end{cases} $$ and $$ \Re \CC^-[\diamond^k](\zeta) =\begin{cases} 0 & k \geq 0 \\ -{\zeta^k + \zeta^{-k} \over 2} & k < 0 \end{cases} $$
Express the solution outside the circle as $$ v(x,y) = \Im ( \E^{-\I \theta} z + \CC f(z)) $$ for a to-be-determined $f$. On the circle, this reduces to $$ \Im \CC^- f(\zeta) = -\cos \theta {\zeta - \zeta^{-1} \over 2 \I} + \sin \theta {\zeta + \zeta^{-1} \over 2} $$ Unlike the real case, we can include imaginary coefficients, thus the solution is $$ f(\zeta) = (\cos \theta + \I \sin \theta) \zeta^{-1} $$ and thus the full solution is $$ v(x,y) = \Im ( \E^{-\I \theta} z - \E^{\I \theta} z^{-1})) $$
In [54]:
θ = 0.1
v = (x,y) -> x^2 + y^2 < 1 ? 0 : imag(exp(-im*θ) * (x+im*y) + exp(im*θ) * (x+im*y)^(-1))
Out[54]:
In [58]:
xx = yy = -5:0.01:5
contour(xx, yy, v.(xx', yy); nlevels=100)
plot!(Circle(); color=:black, legend=false)
Out[58]:
$z^\alpha$ has the limits $z_\pm^\alpha = \E^{\pm \I \pi \alpha} |z|^\alpha$, thus choose $\alpha = -{\theta \over 2\pi}$ where if we take $0 < \theta < 2\pi$ we have $0 < \alpha < 1$ (the case $\theta = 0$ and $\theta = \pi$ are covered by the Cauchy transform, that is ). Then consider $$ \kappa(z) = (z-1)^{-\alpha} (z+1)^{\alpha-1} $$ which has weaker than pole singularities and satisfies $\kappa(z) \sim z^{-1}$. For $-1 < x < 1$ it has the right jump $$ \kappa_+(x) = (x-1)_+^\alpha (x+1)^{1 - \alpha} = \E^{\I \pi \alpha} (1-x)^\alpha (x+1)^{1 - \alpha} = \E^{2\I \pi \alpha} (x-1)_-^\alpha (x+1)^{1 - \alpha} = \E^{2 \I \pi \alpha} \kappa_-(x)= \E^{\I \theta} \kappa_-(x) $$ and for $x < -1$ it has the jump $$ \kappa_+(x) = (x-1)_+^\alpha (x+1)_+^{1 - \alpha} = \E^{\I \pi \alpha}\E^{\I \pi (1-\alpha)} (1-x)^\alpha (-1-x)^{1 - \alpha} = \kappa_-(x) $$ hence $\kappa$ is analytic.
We need to show this times a constant spans the entire space. Suppose we have another solution $\tilde \kappa$ and consider $r(z) = {\tilde \kappa(z) \over \kappa(z)}$. Note by construction that $\kappa$ has no zeros. Then $$ r_+(x) = {\tilde\kappa_+(x) \over \kappa_+(x)} = {\tilde\kappa_-(x) \over \kappa_-(x)} = r_-(x) $$ hence $r$ is analytic on $(-1,1)$. It has weaker than pole singularities because $\kappa(z)^{-1}$ is actually bounded at $\pm 1$. Therefore $r$ is bounded and entire, and thus must be a constant $r(z) \equiv r$, and thence $\tilde \kappa(z) = r \kappa(z)$.
In [59]:
θ =2.3
α = -θ/(2π)
κ = z -> (z-1)^(-α)*(z+1)^(α-1)
κ(0.1+0.0im) - exp(im*θ)*κ(0.1-0.0im)
Out[59]:
In [60]:
κ(100.0)
Out[60]:
In [62]:
phaseplot(-3..3, -3..3, κ)
Out[62]:
We want to mimic the solution of $\phi_+(x) + \phi_-(x)$. So take $$ \phi(z) = \kappa(z) \CC\br[{f \over \kappa_+}](z) =\E^{-\I \theta/2} (z-1)^{-\alpha}(z+1)^{\alpha-1} \CC[f (1-x)^{\alpha}(1+x)^{1-\alpha}](z) $$ This has the jump \begin{align*} \phi_+(x) - \E^{\I \theta}\phi_-(x) = \kappa_+(z) \CC_+\br[{f \over \kappa_+}](x) - \E^{\I \theta}\kappa_-(z)\CC_-\br[{f \over \kappa_+}](x) = \kappa_+(x) \pr({\CC_+\br[{f \over \kappa_+}](x) - \CC_-\br[{f \over \kappa_+}](x) }) = f(x) \end{align*}
Thus the general solution is $\phi(z) + C \kappa(z)$.
In [63]:
θ =2.3
α = -θ/(2π)
κ = z -> (z-1)^(-α)*(z+1)^(α-1)
x = Fun()
κ₊ = exp(im*θ/2)*(1-x)^(-α)*(x+1)^(α-1)
f = Fun(exp)
z = 2+im
φ = z -> κ(z)*cauchy(f/κ₊, z)
φ(0.1+0.0im)-exp(im*θ)*φ(0.1-0.0im) - f(0.1)
Out[63]:
In [64]:
β = 2.3;
x = -2.0
(x+0.0im)^(im*β) - exp(-2π*β)*(x-0.0im)^(im*β)
Out[64]:
We actually have bounded (oscillatory) growth near zero since $$ |\E^{\I \beta \log z}| = |\E^{\I \beta \log |z|} \E^{-\beta \arg z}| = \E^{-\beta \arg z} $$
In [67]:
xx = yy = -1:0.01:1
contourf(xx, yy, abs.((xx' .+ im.*yy).^(im*β)))
Out[67]:
Thus if we write $c = r \E^{\I \theta}$ for $0 < \theta < 2 \pi$ and define $\alpha = -{\theta \over 2 \pi} + \I{\log r \over 2 \pi}$ we can write the solution to 4.1 as $$ \kappa(z) = (z-1)^{-\alpha} (z+1)^{\alpha-1} $$
The same arguments as before then proceed. and the solution to 4.3 is $$ \phi(z) = \kappa(z) \CC\br[{f \over \kappa_+}](z)+ C \kappa(z) $$
In [68]:
θ =2.3
α = -θ/(2π)
κ = z -> (z-1)^(-α)*(z+1)^(α-1)
κ(0.1+0.0im) - exp(im*θ)*κ(0.1-0.0im)
Out[68]:
In [69]:
r = 2.4
θ = 2.1
c = r*exp(im*θ)
α = -θ/(2π) + im*log(r)/(2π)
κ = z -> (z-1)^(-α)*(z+1)^(α-1)
κ(0.1+0.0im)-c*κ(0.1-0.0im)
Out[69]:
Ah, this is a trick question! Note that $z \kappa(z) \sim z^{-1} = O(z)$ and satisfies all the other properties. Thus consider any other solution $\tilde \kappa(z)$ and write $$ r(z) = {\tilde \kappa(z) \over \kappa(z) } $$ This has trivial jumps and hence is entire: for example, on $(a,1)$ we have $$ r_+(x) = {\tilde \kappa_+(x) \over \kappa_+(x) } = {-\tilde \kappa_-(x) \over -\kappa_-(x) } = r_-(x) $$ But since $\kappa \sim O(z^{-2})$ we only know that $\kappa$ has at most $O(z)$ growth, hence it can be any first degree polynomial. Therefore, the space of all solutions is in fact two-dimensional: $\psi(z) = (A + Bz) \kappa(z)$.
Here we mimick the usual solution techniques and propose: $$ \phi(z) = \kappa(z) \CC\br[{f \over \kappa_+}](z) + (A+Bz) \kappa(z) $$ A quick check confirms it has the right jumps: $$ \phi_+(x) = \kappa_+(x) \CC_+\br[{f \over \kappa_+}](x) + (A+Bx) \kappa_+(x) =\kappa_+(x) \left({f(x) \over \kappa_+(x)} + \CC_-\br[{f \over \kappa_+}](x)\right) - (A+Bx) \kappa_-(x) = -\phi_-(x) + f(x) $$
In [71]:
V = x -> x^4
Vp = x -> 4x^3
N = 100
λ⁰ = randn(N) # initial location
prob = ODEProblem((λ,t,_) -> Float64[sum(1 ./(λ[k] .- λ[[1:k-1;k+1:end]])) - Vp(λ[k]) for k=1:N], λ⁰, (0.0, 10.0))
λ = solve(prob; reltol=1E-6);
In [73]:
@gif for t=0.0:0.05:7.0
scatter(λ(t)/N^(1/4) ,zeros(N); label="charges", xlims=(-2,2), title="t = $t")
end
Out[73]:
The limiting distribution has the following form:
In [74]:
histogram(λ(10.0)/N^(1/4); nbins=30, normalize=true, label="histogram of charges")
Out[74]:
We want to solve $$ {\D \lambda_k \over \D t} = \sum_{j=1 \atop j \neq k}^N {1 \over \lambda_k -\lambda_j} - 4\lambda_k^3 $$ Rescale via $\mu_k = {\lambda_k \over N^{1/4}}$ gives $$ 0 = N^{1/4} {\D \mu_k \over \D t} = N^{-1/4} \sum_{j=1 \atop j \neq k}^N {1 \over \mu_k -\mu_j} - 4 N^{3/4} \mu_k^3 $$ or in other words $$ 0 = N^{-1/2} {\D \mu_k \over \D t} = {1 \over N} \sum_{j=1 \atop j \neq k}^N {1 \over \mu_k -\mu_j} - 4 \mu_k^3 $$ We can now formally let $N\rightarrow \infty$ to get our equation $$ \dashint_{-b}^b {w(t) \over x-t} \dt = 4 x^3 $$ where I've used symmetry to assume that the interval is symmetric. We want to find $w$ and $b$ so that this equations holds true and $w$ is a bounded probability density:
Our equation is equivalent to
$$
\HH_{[-b,b]} w(x) = -{4 x^3 \over \pi}
$$
recall the inversion formula
$$
u(x) = {-1 \over \sqrt{b^2 - x^2}}\HH \left[{ f(\diamond) \sqrt{b^2-\diamond^2} }\right](x) - {C \over \sqrt{b^2-x^2}}
$$
In our case $f(x) = -{4 x^3 \over \pi}$ and we use
$$
\sqrt{z-b}\sqrt{z+b} = z\sqrt{1-b/z}\sqrt{1+b/z} = z - {b^2 \over 2 z} -{b^4 \over 8z^3} + O(z^{-4})
$$
to determine
$$
2 \I \CC \left[{ \diamond^3 \sqrt{b^2-\diamond^2} }\right](x) = z^3(\sqrt{z-b}\sqrt{z+b} -z + {b^2 \over 2 z} + {b^4 \over 8z^3}) = z^3\sqrt{z-b}\sqrt{z+b} -z^4 + {b^2z^2 \over 2} + {b^4 \over 8}
$$
In [75]:
b = 5
x = Fun(-b .. b)
(2im)cauchy(x^3*sqrt(b^2-x^2),z)
Out[75]:
Therefore, \begin{align*} u(x) = {4\I \over \pi \sqrt{b^2 - x^2}}(\CC^+ + \CC^-) \left[{ \diamond^3 \sqrt{b^2-\diamond^2} }\right](x) - {C \over \sqrt{b^2-x^2}} \\ {4 \over \pi \sqrt{b^2 - x^2}}(-x^4+{b^2 x^2 \over 2} + {b^4 \over 8})- {C \over \sqrt{b^2-x^2}} \end{align*} We choose $C$ so this is bounded, in particular, we get get the solution $$ u(x) = {4 \over \pi \sqrt{b^2 - x^2}}(-x^4+{b^2 x^2 \over 2} + {b^4 \over 2}) $$
In [76]:
u = 4/(π*sqrt(b^2-x^2))*(-x^4 + b^2*x^2/2 + b^4/2)
hilbert(u, 0.1)
Out[76]:
In [77]:
-4*0.1^3/π
Out[77]:
At least it looks right, we just need to get the right b:
In [78]:
plot(u; label = "b = $b")
Out[78]:
We want to choose $b$ now so that this integrates to $1$. For example, this choice of $b$ is horrible:
In [79]:
sum(u)
Out[79]:
There's a nice trick: If $-2\pi \I \CC u(z) \sim {1 \over z}$ then $\int_{-b}^b u(x) \dx = 1$. We know since $$ {1 \over \sqrt{1+z}} = 1 - {z \over 2} + {3z^2 \over 8} - {5z^3 \over 16} + O(z^4) $$ \begin{align*} {-z^4 + {b^2z^2 \over 2} + {b^4 \over 2} \over \sqrt{z-b}\sqrt{z+b}} &= {-z^3 + {b^2z \over 2} + {b^4 \over 2 z} \over \sqrt{1-b/z}\sqrt{1+b/z}} \\ &= (-z^3 + {b^2z \over 2} )(1 + {b \over 2 z} + {3 b^2 \over 8 z^2} + {5 b^3 \over 16z^3} )(1 - {b \over 2 z} + {3 b^2 \over 8 z^2} - {5 b^3 \over 16z^3}) + O(z^{-1}) \\ &=-z^3 + \pr({b^2 \over 2} +{b^2 \over 4} + {b^2 \over 2} - {3 b^2 \over 8} -{3 b^2 \over 8} ) z +O(z^{-1})\\ &= -z^3 + O(z^{-1}) \end{align*} Thus we know $$ \CC u(z) = {2\I \over \pi} z^3 +{2 \I \over \pi} {-z^4 + {b^2z^2 \over 2} + {b^4 \over 2} \over \sqrt{z-b}\sqrt{z+b}} $$
In [80]:
cauchy(u, z)
Out[80]:
In [81]:
z =100.0im;
2im/π*z^3 + 2im/π*(-z^4 + b^2*z^2/2 +b^4/2)/(sqrt(z-b)sqrt(z+b))
Out[81]:
taking this one term further we find
$$
{-z^4 + {b^2z^2 \over 2} + {b^4 \over 2} \over \sqrt{z-b}\sqrt{z+b}} = -z^3 +{3 b^4 \over 8 z} + O(z^{-2})
$$
Hence we want to choose $b$ so that
$$
-2\I\pi \CC u(z) = {3 b^4 \over 2 z} \sim {1 \over z}
$$
in other words, $b = ({2 \over 3})^{1/4}$
In [82]:
b = (2/3)^(1/4)
x = Fun(-b .. b)
u = 4/(π*sqrt(b^2-x^2))*(-x^4 + b^2*x^2/2 + b^4/2)
sum(u)
Out[82]:
And it worked!
In [83]:
histogram(λ(10.0)/N^(1/4); nbins=25, normalize=true, label="histogram of charges")
plot!(u; label="u",xlims=(-2,2))
Out[83]: